مشكلات تعليم مهارة القراءة وعلاجها بالمدرسة الثانوية الإسلامية المعارف سينجاساري مالانق - Nurul Hana Mustofa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
ولا يمكن بغض النظر عن خطط التعليم الحسنة. فالخطط تحصل على الأغراض المقصودة في عملية التعليم ودوافع الطلاب ومتابعتهم على المشكلات التعليمية. تعليم مهارة القراءة ترتبط بانضباط علم أخر في اللغة العربية. المشكلات في تعليم مهارة القراءة ترى من أوجه مختلفة، لاسيما العلاج لهذه المشكلات. مشكلات تعليم مهارة القراءة وعلاجها بالمدرسة الثانوية الإسلامية المعارف سينجاساري مالانق، ألا وهي: (1) المشكلات اللغوية التي تتضمن على تطبيق تركيبي النحو والصرف، العجز عن فهم المقروء، والقفز عن بعض الكلمات. والمشكلات غير اللغوية التي تتضمن على تنفيذ تعليم مهارة القراءة، إدارة الفصل غير التام، خلفية الطلاب المختلفة، الدوافع التعليمية الضعيفة، الكفاءة المختلفة في الفصل، (2) والعلاج لمشكلات تعليم مهارة القراءة الذي يقدمه المدرسة والمدرس يتضمن على تصنيف الطلاب في فصل واحد بكفاءتهم وخصائصهم وبطريقة برنامج الدراسة المجموعية، و بطريقة الإدراك بالترابط في بداية التعليم، وبطريقة التخطيط والتقويمThe success of the learning process in the classroom is inseparable from the good learning plan. Planning can achieve the desired goal in learning, motivating students and avoid obstacles in the process of learning. Learning Maharah Al Qiroah combines the discipline of Arabic language to another. Problems in learning Maharah Al Qiroah (Reading Skill) can be seen from a different point of view. So do with many solution which appropriate. In this study, the researchers found some findings about the problematic of learning Maharah Al Qiroah in MA Al-Maarif Singosari Malang: (1) linguistic problematic which consists of the application of the theory of the qawaid Nahwu and Sharaf, difficult in understanding a read, and despite a partial word in the sentence of a read. Problematic nonlinguistic consists of the implementation of the learning in the classroom, the conditioning class is insufficient, different background of students, low motivation of learning to read, grouping learners have yet to match the capabilities of each learners, lack of time provided by the school and the evaluation process is less criteria assessment Maharah Al Qiroah. (2) solutions and efforts to decrease problematic of learning Maharah Al Qiroah in class X2 MA Al-Maarif Singosari Malang are there will be students grouping according to their respective capabilities at the time of admissions test participants of new students, through programs of groups study, giving motivation at the apersepsi time in early learning, planning and evaluation.